Governing UK Biobank: the importance of ensuring public trust. - Tutton, R; Kaye, J; Hoeyer, K (2004)
In the autumn of 2003, UK Biobank published the first draft of its Ethics and Governance Framework. Subsequently, this document has been available for interested parties to comment on and the UK Biobank Board of Directors is expected to adopt the final version in 2004. Here, we aim to contribute to this process and highlight to a wider audience some of the inconsistencies in the issues of consent, governance and right of withdrawal that emerge from the draft of the Framework. These issues will have implications for securing the public trust and long-term support that the success of the project depends on. Therefore, they must be considered carefully because the UK Biobank will be the first ever genetic database of a general population of this size to become operational, and will be used as a model for other projects of this kind.